Improving Teachers' Innovative Work Behavior Through Strengthening School Culture, Self-Efficacy And Work Motivation - Rizca Praztica Syam; Eka Suhardi; Eri Sarimanah (Universitas Pakuan, 2026)
This study aims to analyze the effects of school culture, self-efficacy, and work motivation on teachers’ innovative work behavior. A quantitative approach was employed using a survey method and path analysis. The sample consisted of 106 permanent foundation teachers from six private vocational high schools in Cisaat District, Sukabumi Regency, selected through a saturated sampling technique. The results revealed that school culture, self-efficacy, and work motivation have positive and significant effects on teachers’ innovative work behavior. School culture and self-efficacy also have positive and significant effects on work motivation. Furthermore, work motivation mediates the effects of school culture and self-efficacy on teachers’ innovative work behavior. These findings indicate that strengthening school culture, enhancing self-efficacy, and improving work motivation are important strategies for fostering teachers’ innovative work behavior.